Penampilan Ayam Pedaging yang Mengkonsumsi Pakan Mengandung Tepung Kulit Nanas Disuplementasi dengan Yoghurt - Nurhayati Nurhayati (Jurnal Agripet, 2013)
Broiler chicken performance feed ration containing pineapple peel meal and supplemented by yoghurtABSTRACT. An experiment was conducted to determine the broiler performance feed ration contained pineapple peel meal supplemented by yoghurt. A hundred broiler chickens 2 days old were used in this study those divided into 4 treatment groups and kept for 4 weeks. The treatments were level of pineapple peel meal (PPM) into the ration; P0 = ration without PPM, P1 = ration contained 5 % of PPM, P2 = ration contained 10 % of PPM and P3 = ration contained 15 % of PPM. To neutralize high crude fiber content in the ration, chickens were supplemented by yoghurt consisted 3,3 x 108 CFU/ml of Lactobacillus bulgaricus and Streptococcus thermophilus as much as 3 ml/kg body weight. Yoghurt was offered in the morning before feeding. Each treatment was replicated 5 times. The experiment was assigned into Completely Randomized Design with 4 treatments and 5 replications. Parameters were feed consumption, water consumption, body weight gain and feed conversion ratio. Data were analyzed by Analysis of variance (ANOVA) and significantly effect was tested by Duncans Multiple Range Test. Results of this study showed that there was no significant difference (P0.05) among 0, 5, and 10 % the treatment groups on feed consumption, water consumption, body weight gain and feed conversion ratio. Offered 15 % of pineapple peel to the chickens did not significantly (P0.05) increased feed consumption and conversion ratio but did not significantly (P0.05) decreased body weight gain. It is concluded that pineapple peel meal might be mixed into the broiler chicken ration up to 10 % without any significant adverse effect on performance when they were supplemented by yoghurt as much as 3 ml/kg of body weight.